Organization of health at physical training lessons in the modern school - Nikolai Gorodysky; Eugene Shalenko (Kharkiv State Academy of Physical Culture, 2016)
Purpose: to identify and outline the necessary conditions aimed at a healthy lifestyle, refusal of bad habits, providing health care of students at physical education classes. Material & Methods: theoretical and practical achievements of modern scientists, authors experience in conducting physical education classes; analysis of scientific literature on selected issues, systematization of received theoretical results and acquired sports and teaching experience, generalization of acquired scientific data to formulate conclusions of the article. Results: in solving the problem of defining the role of the designated teacher who seeks to convince students in healthy lifestyles. Conclusions: ensuring longevity in modern conditions of life requires public awareness about the need for healthy lifestyles and instilling in youth the love for the physical training and sports.